2007
DOI: 10.1167/iovs.07-0002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th-1 Chemokines and Chemokine Receptors on the Ocular Surface of C57BL/6 Mice: Effects of Desiccating Stress

Abstract: Specific patterns of Th-1 and -2 chemokines and their receptors are induced in the mouse ocular surface by desiccating stress in a strain-related fashion. Desiccating stress potently stimulates the expression of Th-1 cell-attracting chemokines and chemokine receptors on the ocular surface of C57BL/6 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 38 publications
3
143
0
1
Order By: Relevance
“…28 Autoreactive CD4 þ T cells are recruited to the ocular surface by chemokines such as CCL2, CCL5, and CXCL9-11, leading to immune-mediated ocular surface damage. 7,25 TLR4 ligation results in the production of proinflammatory cytokines such as IL-1b, IL-6, and TNF that promote the activation of leukocytes and lymphocytes. 10,29 TLR4 signaling is important for the activation of APC-and T-cell-mediated immunoinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Autoreactive CD4 þ T cells are recruited to the ocular surface by chemokines such as CCL2, CCL5, and CXCL9-11, leading to immune-mediated ocular surface damage. 7,25 TLR4 ligation results in the production of proinflammatory cytokines such as IL-1b, IL-6, and TNF that promote the activation of leukocytes and lymphocytes. 10,29 TLR4 signaling is important for the activation of APC-and T-cell-mediated immunoinflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Toll-like receptors (TLRs) are pattern recognition receptors of the innate immune system that recognize highly conserved microbial structures and products.…”
Section: Purposementioning
confidence: 99%
“…33 To investigate the possibility that ICAM-1 is necessary for expression of chemokines that attract ␥␦ T cells, we assessed epithelial mRNA levels for an array of chemokines reported to be chemotactic for ␥␦ T cells. Limbal and paralimbal epithelium (ie, the regions not directly injured during abrasion) was collected from wild-type and ICAM-1 Ϫ/Ϫ mice, either uninjured or 3 hours after central epithelial abrasion.…”
Section: Icam-1 and Chemokine Expression By Corneal Epitheliummentioning
confidence: 99%
“…After activation, Th cells can differentiate into Th-1, Th-2, Th-3, and Th-17 subtypes. Studies have shown that Th-1 and Th-17 cells are correlated with the pathogenesis of dry eye (Stern et al, 2005;Yoon et al, 2007;De Paiva et al, 2009;El Annan et al, 2009;Zheng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%